2014
DOI: 10.1104/pp.113.232660
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Roles for Maize PAN1 and PAN2 Receptor-Like Proteins in Cytokinesis and Cell Morphogenesis

Abstract: Pangloss1 (PAN1) and PAN2 are leucine-rich repeat receptor-like proteins that function cooperatively to polarize the divisions of subsidiary mother cells (SMCs) during stomatal development in maize (Zea mays). PANs colocalize in SMCs, and both PAN1 and PAN2 promote polarization of the actin cytoskeleton and nuclei in these cells. Here, we show that PAN1 and PAN2 have additional functions that are unequal or divergent. PAN1, but not PAN2, is localized to cell plates in all classes of dividing cells examined. pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 57 publications
(102 reference statements)
2
34
0
Order By: Relevance
“…Interestingly, in fission yeast53 and in the slime mold Dictyostelium discoidea 54, LRR containing proteins have been associated with cytokinesis. Similarly, plant LRR proteins have been linked to cytokinesis as well55565758.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in fission yeast53 and in the slime mold Dictyostelium discoidea 54, LRR containing proteins have been associated with cytokinesis. Similarly, plant LRR proteins have been linked to cytokinesis as well55565758.…”
Section: Discussionmentioning
confidence: 99%
“…Polar localization of this complex is a prerequisite for recruitment of receptor-like kinases (RLKs) PAN2 and PAN1, both polarly localized at the end of SMC proximal to GMC (Cartwright et al 2009;Zhang et al 2012). Afterwards, Rho-GTPases of plants (ROPs) are recruited to the polar SMC site (Humphries et al 2011;Sutimantanapi et al 2014;Facette et al 2015). Besides, phospholipases C and D are necessary for the perception or the transduction of the stimulus emitted by the GMCs (Apostolakos et al 2008), whereas auxin stimulation is accomplished by the catalytic activity of phosphatidylinositol-3-kinase (PI3K; Livanos et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…55,56 Considering that PAN1 and ROPs cooperate on positioning SMC nucleus and that in pan1 mutants AF-patches were absent, 54,55 it may be suggested that PAN1 may generally interfere with cortical AF-organization. This protein also accumulates at definite regions of subsidiary cells and intervening cells of stomatal rows of Z. mays, 57,58 where distinct AF accumulations have also been found. 34,58 Thus, the AF-patches at the polar end of Z. mays SMCs, should not be considered as prime polarizing factors, since they are absent from SMCs in other grasses like Triticum turgidum, but they may be related to the local SMC bulging toward the inducing GMC.…”
Section: Auxin Signaling and Induction Of Smc Divisionmentioning
confidence: 86%
“…This protein also accumulates at definite regions of subsidiary cells and intervening cells of stomatal rows of Z. mays, 57,58 where distinct AF accumulations have also been found. 34,58 Thus, the AF-patches at the polar end of Z. mays SMCs, should not be considered as prime polarizing factors, since they are absent from SMCs in other grasses like Triticum turgidum, but they may be related to the local SMC bulging toward the inducing GMC. 12,34 Evidence favoring this hypothesis is that in TIBA-and LY294002-treated SMCs, where the polar nucleus migration and the asymmetrical division were inhibited, AF-patches were assembled.…”
Section: Auxin Signaling and Induction Of Smc Divisionmentioning
confidence: 86%